2018
DOI: 10.1007/s00262-018-2263-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory functions of PD-L1 and PD-L2 in the regulation of anti-tumor immunity in murine tumor microenvironment

Abstract: PD-L1 expressed on tumor cells and bone marrow-derived hematopoietic cells, as well as PD-L2 inducibly expressed on tumor-associated macrophages, play an important role in the suppression of anti-tumor immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…To our knowledge, this is the first report to directly show the functional consequence of the immunosuppressive role of PD-L2 in a human model, although two reports recently proved the antitumor activity of PD-L2 using a preclinical animal model [44,47]. In the present study, using tumor antigen-specific CTL clone, we clearly showed that anti-PD-L2 mAb significantly enhanced the cytotoxicity of CTLs against GC cell lines expressing PD-L2 (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…To our knowledge, this is the first report to directly show the functional consequence of the immunosuppressive role of PD-L2 in a human model, although two reports recently proved the antitumor activity of PD-L2 using a preclinical animal model [44,47]. In the present study, using tumor antigen-specific CTL clone, we clearly showed that anti-PD-L2 mAb significantly enhanced the cytotoxicity of CTLs against GC cell lines expressing PD-L2 (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…The tendency of EGFR ‐mutated NSCLC with high PD‐L1 expression to coexpress PD‐L2 through extrinsic or intrinsic mechanisms remains elusive in the context of basic research. However, the observation of highest PD‐L2 coexpression in type 1 tumors compared to other TME types could be reasonable evidence that type 1 tumors might benefit better from anti‐PD‐1 therapies than from anti‐PD‐L1 therapies in the clinical context . Further clinical evaluation is warranted to support this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…ICB treatment primarily targets programmed cell death 1 (PD-1), programmed cell death-ligand 1 (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) (Sharma et al, 2017). Programmed cell death-ligand 2 (PD-L2) was found to play a role in the regulation of anti-tumor immunity (Umezu et al, 2019). Multiple studies have shown that tumor mutational burden (TMB) may be a surrogate for overall neoantigen load, and it is correlated with clinical benefit from multiple checkpoint inhibitors (Rizvi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%